Comparision the effect of high intensity interval training and continuous endurance training on expression of MYOD in Soleus muscle of diabetic rats - زهرا سلیمانی; مقصود پیری (Shahid Beheshti University, 2016)
Purpose:Due to the development of diabetes and complications of the disease such as Muscular Atrophy, AndConsidering the role of exercise in the management of symptoms, The purpose of this study was to Comparison of highintensity interval training with continuous endurance training on expression of Myod in diabetic rats. Material &Methods: 21 Male Wistar rats with an average weight 260 ± 10g, after induction of diabetes by streptozotocin wererandomly divided into 3 groups: control, continuous endurance, intensity interval. The training program was conductedfive days a week for five weeks. Endurance training sessions was 30 minutes running on treadmill with intensity of about60% VO2max. In intensity interval group the program was four frequency of 3 minutes of 85 to 90% VO2max and oneminute recovery between each frequency with 30 to 35% VO2max, Gene expression of Myod was measured by themethod of qREAL TIME PCR. Results: The One-way analysis of variance showed a significant increase the expressionof Myod in high intensity interval group compared to continuous endurance(p<0.05) and control groups (p<0.05); Butthere was no significant difference between continuous endurance and control groups. Conclusions: Due to the highintensity interval training seems to be severe, with induction of gene expression of Myod may be an effective interventionfor reducing muscle atrophy in patients with diabetes, while the high volume of moderate-intensity exercise (endurance)on this aspect of diabetes effect not significant.